The Role Of Religiosity, Tax Knowledge, And Tax Sanctions On Tax Compliance Of MSMEs In Malang City - Sheila Nur Eltanin; Sitinjak, Norman Duma (LP2M IAIN Palopo, 2025)
The purpose of the study was to test religiosity, knowledge and tax sanctions on taxpayer compliance of MSMEs. The study used a quantitative research method with multiple linear regression analysis in the influence test. The number of respondents in the study was 100 people. The sampling technique chosen was purposive sampling. Respondents were MSME owners in 5 sub-districts in Malang City. The findings of the study showed that religiosity, tax knowledge, and tax sanctions had an effect on taxpayer compliance of MSMEs in Malang City. The greatest influence was given by tax sanctions. MSME actors in Malang City are more tax compliant because of tax sanctions